(untitled) (Eurasian Journal of Ecology, 2016)
Considered the main fish breeding and biological indicators of whitefish in steppe lakes of Kazakhstan of different ecotypes: freshwater, crucians, saltwater and freshwater perch-carpentry. Described morphological characteristics of the hybrid ripus with whitefish-ladoga and highlights of its biology.